Implementasi Prinsip Syariah Dalam Praktik Leasing Syariah - Aulia Maudy; Qonita Febriyani; Hermina Pristilia; Lilis Nurrohmah; Ria Anisatus Solihah; Muhammad Taufiq Abadi (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
This article aims to explore whether the application of Islamic principles has been properly implemented in Islamic leasing institutions. The sharia label on Islamic financial institutions implies several consequences in the system and operational concepts that must comply with sharia principles. This type of research uses a literature study with descriptive research methods. Sharia does not lie in the term musyarakah or mudharabah alone which in practice sometimes contradicts the value of Islam itself. In its application, there are many leasing companies that apply the principles of Islamic law, but some leasing companies labelled as sharia are not in accordance with the principles of Islamic law because they are still very profit-oriented